Childhood Abuse Is Related to Working Memory Impairment for Positive Emotion in Female University Students. (February 2014) - Cromheeke, Sofie; Herpoel, Laure-Anne; Mueller, Sven C.
Childhood abuse is an important risk factor for depression, anxiety disorders, and substance use later in life. One possible mechanism underlying this association could be deficits in cognitive processing of emotional information. This study tested the impact of distracting emotional information on working memory performance in 21 young women with a history of sexual and physical abuse during childhood/adolescence (mean age = 20.0), and compared their performance to 17 individuals reporting nonabuse-related childhood stress (mean age = 19.6) and a control group of 17 women without a history of childhood stress (mean age = 20.0). During the most difficult distractor condition, working memory accuracy for positive versus neutral incidental emotional stimuli was reduced in women reporting a history of abuse relative to both control groups (with and without nonabuse-related childhood stress). The current results reveal aberrant responses to positive stimuli and are consistent with the notion of persistent influence of childhood abuse on processes critical for emotional well-being and emotion control.